Mutual insurance in Russia: the current state and further development perspectives - E. A. Majukhovskii (Путеводитель предпринимателя, 2020)
The article examines the current state of the mutual insurance market in Russia. It gives a brief review of the legislation in the field of mutual insurance and its significant changes in recent years. There are also basic showing of Russian mutual insurance companies (MIC) at the present time and their dynamics as well. The article shows the problems that hinder the development of MIC. Basing on the analysis of the situation, there is given the forecast of further development of the national mutual insurance market.